The OEIS is supported by the many generous donors to the OEIS Foundation.

 Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 60th year, we have over 367,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”). Other ways to Give
 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A351771 Given g.f. A(x), the even bisections of both A(x) and A(x)^2 are equal, and the odd bisections of both A(x)^2 and A(x)^3 are equal (after the initial terms). 3
 1, 1, -1, 3, -7, 28, -79, 350, -1075, 5020, -16180, 78023, -259417, 1278340, -4343642, 21740636, -75065787, 380161308, -1328887420, 6792111260, -23975385148, 123448657904, -439228736887, 2275311657814, -8148868193557, 42427160829508, -152792221834364 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,4 COMMENTS a(2*n+1) = A352383(n) for n >= 0. LINKS Table of n, a(n) for n=0..26. FORMULA G.f. A(x) satisfies: (1a) [x^(2*n)] A(x) = [x^(2*n)] A(x)^2 for n >= 1. (1b) [x^(2*n+1)] A(x)^2 = [x^(2*n+1)] A(x)^3 for n >= 1. (1c) [x^(2*n+1)] A(x)^3 = [x^(2*n+1)] A(x)^4 for n >= 1. (2) (A(x) - A(-x))/2 = x/(A(x)*A(-x)). (3a) (A(x)^2 + A(-x)^2)/2 = (A(x) + A(-x))/2. (3b) (A(x)^2 - A(-x)^2)/2 = 2*x + (A(x) - A(-x))^3/2. (4) A(x)^2 = 2*x + (A(x) + A(-x))/2 + (A(x) - A(-x))^3/2. (5a) A(x)^2 = 2*x + (A(x)^2 + A(-x)^2)/2 + (A(x) - A(-x))^3/2. (5b) A(x)^3 = 3*x + (A(x)^3 + A(-x)^3)/2 + (A(x) - A(-x))^3/2. (5c) A(x)^4 = 4*x + (A(x)^4 + A(-x)^4)/2 + (A(x) - A(-x))^3/2. (6) A(x)^4 - A(x)^3 = x + x*(A(x) - A(-x)). (7) A(-x) = (A(x)^2 + sqrt(A(x)^4 - 8*x*A(x)))/(2*A(x)). (8) (A(x) - A(-x))^3/2 = 4*x*F(x^2), where F(x) = Series_Reversion( x*(1+x)^3/(1+2*x)^6 ). (9) A(x)^2 - A(x) = Series_Reversion( x - x*(C(x) + C(-x))/2 ), where C(x) = x + C(x)^2 is the Catalan power series (A000108). (10) A(x) = 1 + Series_Reversion( x*(1+x)*(3 + 2*x + sqrt(1-4*x-4*x^2))/4 ). (11) 0 = 2*x^2 + A(x)*(1 - A(x))*(1 + 2*A(x))*x + A(x)^4*(1 - A(x))^2. EXAMPLE G.f. A(x) = 1 + x - 1*x^2 + 3*x^3 - 7*x^4 + 28*x^5 - 79*x^6 + 350*x^7 - 1075*x^8 + 5020*x^9 - 16180*x^10 + 78023*x^11 + ... Compare A(x) with the coefficients in the following series expansions: A(x)^2 = 1 + 2*x - 1*x^2 + 4*x^3 - 7*x^4 + 36*x^5 - 79*x^6 + 444*x^7 - 1075*x^8 + 6324*x^9 - 16180*x^10 + 97872*x^11 + ... A(x)^3 = 1 + 3*x + 0*x^2 + 4*x^3 - 3*x^4 + 36*x^5 - 40*x^6 + 444*x^7 - 579*x^8 + 6324*x^9 - 9000*x^10 + 97872*x^11 + ... A(x)^4 = 1 + 4*x + 2*x^2 + 4*x^3 + 3*x^4 + 36*x^5 + 16*x^6 + 444*x^7 + 121*x^8 + 6324*x^9 + 1040*x^10 + 97872*x^11 + ... which illustrate the properties that the coefficients of x^k for even k in A(x) and A(x)^2 are equal, and that the coefficients of x^k for odd k > 1 in A(x)^2, A(x)^3, and A(x)^4 are equal. Related series. (1) Notice that A(x)^2 - A(x) forms an odd function: A(x)^2 - A(x) = x + x^3 + 8*x^5 + 94*x^7 + 1304*x^9 + 19849*x^11 + 320600*x^13 + 5396108*x^15 + ... such that the series reversion begins Series_Reversion( A(x)^2 - A(x) ) = x - x^3 - 5*x^5 - 42*x^7 - 429*x^9 - 4862*x^11 - 58786*x^13 - ... which equals x - x*(C(x) + C(-x))/2, where C(x) = x + C(x)^2: C(x) = x + x^2 + 2*x^3 + 5*x^4 + 14*x^5 + 42*x^6 + 132*x^7 + 429*x^8 + 1430*x^9 + 4862*x^10 + ... and is the Catalan power series C(x) = (1 - sqrt(1-4*x))/2. (2) Also, the coefficients in the following series form a bisection of A(x): (A(x)^4 - A(x)^3 - x)/2 = x^2 + 3*x^4 + 28*x^6 + 350*x^8 + 5020*x^10 + 78023*x^12 + 1278340*x^14 + ... + A352383(n)*x^(2*n+2) + ... (3) Further, a series bisection of A(x)^2, A(x)^3, and A(x)^4 is (A(x) - A(-x))^3/2 = 4*x^3 + 36*x^5 + 444*x^7 + 6324*x^9 + 97872*x^11 + 1598940*x^13 + 27136744*x^15 + ... + 4*A352384(n)*x^(2*n+3) + ... which is equal to 4*x*F(x^2), where F( x*(1+x)^3/(1+2*x)^6 ) = x, and F(x) = x + 9*x^2 + 111*x^3 + 1581*x^4 + 24468*x^5 + 399735*x^6 + 6784186*x^7 + ... + A352384(n)*x^(n+1) + ... with (F(x)/x)^(1/3) = 1 + 3*x + 28*x^2 + 350*x^3 + 5020*x^4 + 78023*x^5 + 1278340*x^6 + ... + A352383(n)*x^n + ... (4) The above observations lead to the composition of functions Series_Reversion(A(x) - 1) = [x - x*(C(x) + C(-x))/2] o (x + x^2) which is equivalent to Series_Reversion(A(x) - 1) = x*(1+x)*(3 + 2*x + sqrt(1-4*x-4*x^2))/4. MATHEMATICA CoefficientList[1 + InverseSeries[Series[x*(1 + x)*(3 + 2*x + Sqrt[1 - 4*x - 4*x^2])/4, {x, 0, 30}], x], x] (* Vaclav Kotesovec, Mar 15 2022 *) PROG (PARI) /* Using Series Reversion */ {a(n) = my(A = 1 + serreverse( x*(1+x)*(3 + 2*x + sqrt(1-4*x-4*x^2 +x^2*O(x^n)))/4)); polcoeff(A, n)} for(n=0, 30, print1(a(n), ", ")) (PARI) /* From [x^(2*n)] A(x) - A(x)^2 = 0 and [x^(2*n+1)] A(x)^2 - A(x)^3 = 0 */ {a(n) = my(A = 1 + x +x^2*O(x^n)); for(k=2, n, if(k%2==0, A = A + x^k*polcoeff(A^1 - A^2, k), A = A + x^k*polcoeff(A^2 - A^3, k))); polcoeff(A, n)} for(n=0, 30, print1(a(n), ", ")) CROSSREFS Cf. A352383, A352384, A000108. Sequence in context: A148755 A148756 A352701 * A148757 A148758 A054277 Adjacent sequences: A351768 A351769 A351770 * A351772 A351773 A351774 KEYWORD sign AUTHOR Paul D. Hanna, Mar 14 2022 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified December 8 13:24 EST 2023. Contains 367679 sequences. (Running on oeis4.)